Antenatal Three-Dimensional Printing for Ex Utero Intrapartum Treatment Procedures - Garcia de Paredes, Jessica; Gosnell, Jordan; Strug, Michael; Giuliani, Emma; Thakur, Mili; Romero, Vivian C; Cordoba, Marcos (Obstetrics and gynecology (New York. 1953), 2022)
Prenatal ultrasonography allows for timely identification of fetal abnormalities that can have an effect on securing the neonatal airway at delivery. We illustrate the role of antenatal three-dimensional printing in cases with fetal airway obstruction. We present two cases that highlight the utility of a three-dimensional printing technique to aid in ex utero intrapartum treatment procedures during cesarean delivery. Three-dimensional printing plays a complementary role to standard imaging options in optimizing presurgical planning, prenatal parental counseling, personalized patient care, and education of the multidisciplinary team in cases of fetal congenital airway obstruction.